2022
DOI: 10.1021/acsomega.2c03745
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Surface Roughness of Different Sustainable Dental Composite Blocks: Comprehensive In Vitro Study

Abstract: The study purposed to investigate the biocompatibility and sustainability of two computer-aided design/computer-aided manufacturing (CAD/CAM) resin-based composites compared to a resin-modified ceramic in terms of surface roughness, biofilm formation, cytotoxicity, genotoxicity, and cellular changes observed under transmission electron microscopy (TEM). Three CAD/CAM blocks were used, two resin-based composites [Brilliant Crios (BC) and Cerasmart, (CS) and one hybrid ceramic (Vita Enamic (EN)]. Each block was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…According to the author’s classification, one can affirm that some of the CAD/CAM restorative materials tested in the present study are moderately cytotoxic (e.g., CS_C powder on BJ cells at all concentrations tested and TC_C powder, only at concentrations of 1 mg/mL and 0.5 mg/mL, Figure 6 ; as well as SN_B powder on HaCaT cells at a concentration of 0.2 mg/mL, Figure 7 ). Our results are in agreement with the literature [ 17 , 34 , 51 , 52 ]. An explanation of this acute cytotoxicity recorded in the case of CS restorative material, exposed to an acidic environment could be related to the ions leaching from nanoceramic resin when the CS material was immersed in a cell culture medium.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the author’s classification, one can affirm that some of the CAD/CAM restorative materials tested in the present study are moderately cytotoxic (e.g., CS_C powder on BJ cells at all concentrations tested and TC_C powder, only at concentrations of 1 mg/mL and 0.5 mg/mL, Figure 6 ; as well as SN_B powder on HaCaT cells at a concentration of 0.2 mg/mL, Figure 7 ). Our results are in agreement with the literature [ 17 , 34 , 51 , 52 ]. An explanation of this acute cytotoxicity recorded in the case of CS restorative material, exposed to an acidic environment could be related to the ions leaching from nanoceramic resin when the CS material was immersed in a cell culture medium.…”
Section: Discussionsupporting
confidence: 94%
“…Considering cytotoxicity, BC showed the highest values, followed by CS and EN. Consequently, EN was considered the most biocompatible material among the tested ones [ 34 ]. Another study reported the biocompatibility of Tetric CAD and eight other resin materials [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The water absorption capacity and solubility are important indexes to evaluate the repair effect of restorative materials. When the aqueous solution comes into contact with the dental material, the water molecules can penetrate and diffuse into the polymer chains of the material, causing the material to slightly expand or deform, leading to its separation from the tooth or even fall out. , The solubility of dental restorative materials can cause dimensional instability, crack formation, and loosening of the material under internal stress and eventually lead to the fracture of the restorative material . Therefore, the water absorption capacity (Figure d) and solubility (Figure e) of DRCs are evaluated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…More precisely, after a thorough investigation of the recent literature concerning biofilm formation on resin-based CAD/CAM blocks for permanent indirect restorations, a total of eleven research articles were found [69][70][71][72][73][74][75][76][77][78][79]. These studies investigated one or more hybrid, resin-based CAD/ CAM materials with regard to biofilm attachment and growth.…”
Section: Research On Biofilm Formation On Resin-based Hybrid Cad/cam ...mentioning
confidence: 99%
“…The materials investigated in each study differed. Some researchers solely examined resinbased CAD/CAM blocks [70,[76][77][78]. Others compared resin-based CAD/CAM blocks to conventional composite resins [74], whereas some in vitro research incorporated direct composite resins, indirect CAD/CAM blocks and human enamel [72,73].…”
Section: Research On Biofilm Formation On Resin-based Hybrid Cad/cam ...mentioning
confidence: 99%